Tensions and Contradictions: A Study of Charity Shop Workers in the Digital Age - Burke, Maria; Peters, Jasmine; Petterson, Malin (Bobcatsss, 2023)
The purpose of this paper is to present a set of collected views concerning an exploration of tension between the retailing of old or vintage items in today’s new digital age. In particular to consider the ‘Digital Transformation’ of the artefacts by exploring views and opinions of workers. This study explored the social perspectives regarding tensions and contradictions between the function of the charity shop whose primary purpose is to “recycle” pre-loved, pre-owned, memory laden products, often labelled as “vintage” within a 21st century setting where new digital technologies are accepted as part of our everyday life. This regional study of “Digital Transformation” took place in (pre-COVID) South East England, in the cities of Chichester, Salisbury and Winchester. These cities were chosen as each has a strong cultural identity, such as historical monuments, cathedrals, museums and a range of National Heritage sites, which make these cities popular and attractive to tourists. As a result, these high streets have become prime retail spaces for shops and cafes, - and ideal locations for charity shops, which provided the setting for the research. The research methodology needed to allow for cultural differences between the shops whilst still taking into account the similarity of their organisational purpose. In order to allow for, and yet explore this tension, an interpretivist approach was employed using semi-structured interviews to collect the empirical data. The contribution of the work is in terms of providing a previously unseen “body of opinion” that may act as a marker for future generations exploring the life and digital transformation of charity shop workers in the digital age. The work will also be useful for museums and heritage institutions who deal with vintage artefacts.